Unveiling ubiquitinome rearrangements induced by Salmonella infection. Issue 9 (1st September 2016) - Bionda, Tihana; Behrends, Christian
ABSTRACT: Ubiquitination plays a critical role in the activation of host immune responses to infection and serves as a signal for pathogen delivery to phagophores along the xenophagy pathway. We recently performed systematic ubiquitination site profiling of epithelial cells infected with Salmonella Typhimurium. Our findings specifically highlight components of the NFKB, membrane trafficking pathways and RHO GTPase systems as ubiquitination hubs during infection. In addition, a broad spectrum of bacterial effectors and several outer membrane proteins are ubiquitinated in infected cells. This comprehensive resource of ubiquitinome dynamics during Salmonella infection enables further understanding of the complex host-pathogen interplay and may reveal novel targets for the inhibition of Salmonella invasion and inflammation.